Lazarsfeld's wives, or: what happened to women sociologists in the twentieth century. Issue 1 (2nd January 2021) - Fleck, Christian
ABSTRACT: The paper compares the lives of three female social scientists born in the first two decades of the twentieth century and belonging to the first generations that had the opportunity not only to study at universities, but also to realistically consider a professional career in academia. Marie Jahoda, Herta Herzog and Patricia L. Kendall made their ways separately and interacted only rarely with each other, but shared at least one characteristic which influenced their careers: they were married to Paul F. Lazarsfeld, one of the eminent sociologists of the twentieth century, prominent as someone who encouraged and supported many of his collaborators and students. The comparison of these three women shows that they were professionally successful but did not completely prioritize academic work before other interests, ambitions, and obligations. These priorities found a correspondence in their underperformance in academia with regard to the particular preconditions to enter the pantheon of an academic discipline. Both their oeuvres and their academic records suggest that they were not actively striving to become academic 'immortals.' Here it is shown that women, even if they are to be located below the 'ultra elite, ' produced remarkable and memorable intellectual achievements.